Islamic Educational Values In The Contemporary Banjar Betapung Tawar Tradition - Mutia Rahmawati; Nuril Khasyi’in; Sheila Rosalia; Reza Setya Rachman; Muhammad Fadhilah (Penerbit Presisi Pustaka, 2026)
This study aims to re-examine the meaning of the Betapung Tawar tradition from an Islamic educational perspective and to analyze efforts to revitalize its spiritual values in the contemporary era. Betapung Tawar is one of the cultural heritages of the Banjar community that embodies religious and social values and reflects the integration of local culture with Islamic teachings. However, amid modernization and globalization, its spiritual meaning has shifted, particularly among younger generations who tend to perceive it merely as a cultural ceremony. This study employs a qualitative-descriptive approach through literature review and cultural observation of the Banjar society. The findings indicate that the Betapung Tawar tradition contains core Islamic educational values, including tauhid (monotheism), prayer, moral discipline, and social solidarity, which align with the principles of Islamic law. The revitalization of these values can be implemented through Islamic cultural education in schools, culture-based da’wah, and the active involvement of younger generations in local wisdom-based activities. Thus, the Betapung Tawar tradition is not only preserved as cultural heritage but also functions as a medium for the internalization and transmission of Islamic educational values in contemporary Banjar society.